2011
DOI: 10.1002/psp.615
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and selectivity in Brazilian migration to Japan and the United States

Abstract: This research analyses the composition of Brazilian migrants in two case studies, comparing the demographics of first‐time migrants over time in the network between Maringá, Brazil and Japan with that between Criciúma, Brazil and the US. Couched primarily within migrant social network theory, the research explores how the legal framework operating in each case influences the level and composition of Brazilian migration over time. Brazilian migration to Japan generally occurs within the context of a legally reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…A second line of critique can be drawn from studies that have shown that contexts of destination and departure also influence migrants' use of available networks (Villarrubia-Mendoza 2016; Zell and Skop 2011;Côté et al 2015;Gold 2001;Bagchi 2001). It is therefore misleading to assume a general pattern in the role of migrant networks in migration, regardless of contexts of arrival or departure.…”
Section: Revisiting 'Migrant Network' As Facilitators Of Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…A second line of critique can be drawn from studies that have shown that contexts of destination and departure also influence migrants' use of available networks (Villarrubia-Mendoza 2016; Zell and Skop 2011;Côté et al 2015;Gold 2001;Bagchi 2001). It is therefore misleading to assume a general pattern in the role of migrant networks in migration, regardless of contexts of arrival or departure.…”
Section: Revisiting 'Migrant Network' As Facilitators Of Migrationmentioning
confidence: 99%
“…Furthermore, research suggests that there is a difference in the types of networks used by different occupational classes (Gold 2001). Some argue that the highly skilled rely less on migrant networks than unskilled or undocumented migrants (Zell and Skop 2011), whereas others asserts that undocumented migrants rely less on family networks due to migration restrictions (Collyer 2005). Furthermore, despite the rapid growth of the share of students in migration flows, the study of international student migration is a relatively neglected field of study (King and Raghuram 2013), calling for more research to be done on the question of how students migrate and receive assistance (Raghuram 2013).…”
Section: Revisiting 'Migrant Network' As Facilitators Of Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, no mention is usually made of Brazilian women who migrate to marry a native resident of the destination country. In the US, the population is largely irregular (Margolis, 1994;Zell and Skop, 2011), while in countries like Japan and Portugal the Brazilian population seems to be largely regular (Padilla, 2006;Zell and Skopp, 2011). Other dividing lines than legal status hence come up in such countries.…”
Section: Beyond Communitymentioning
confidence: 99%
“…Padilla states that Brazilians in Portugal were also financially better off than most other migrants. Other research shows that migration policies may affect the role social networks play for specific types of migration (Zell and Skop, 2011). As a result, Brazilians in Portugal have better opportunities than the Brazilians in Amsterdam, leading to different social relations.…”
mentioning
confidence: 99%